Pengaruh Kompetensi, Kepemimpinan Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk Dan Keluarga Berencana (DP3AP2KB) Kabupaten Probolinggo - Asmiati, Asmiati; Hermawan, Dedi Joko; Nafis, Raihan Wishal (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The aim of this research is to determine the extent to which competency, leadership and communication variables partially influence employee performance at DP3AP2KB Probolinggo Regency. A type of quantitative research that utilizes a causal associative approach is used in this research, where Competence, Leadership and Communication are the independent variables and Performance is the dependent variable. The population is all DP3AP2KB Probolinggo Regency employees with a sample of 41 respondents and a saturated sampling technique. The quantitative descriptive method using the SmartPLS program was used to analyze this data, which includes convergent validity test, discriminant validity test, reliability test, normality test, R square test, Q square test and hypothesis test. The test results show: 1) competency has a positive and significant effect on employee performance, 2) leadership does not have a positive and significant effect on employee performance, 3) communication has a positive and significant effect on employee.